10+2(z-5)=-5z+1

Simple and best practice solution for 10+2(z-5)=-5z+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10+2(z-5)=-5z+1 equation:


Simplifying
10 + 2(z + -5) = -5z + 1

Reorder the terms:
10 + 2(-5 + z) = -5z + 1
10 + (-5 * 2 + z * 2) = -5z + 1
10 + (-10 + 2z) = -5z + 1

Combine like terms: 10 + -10 = 0
0 + 2z = -5z + 1
2z = -5z + 1

Reorder the terms:
2z = 1 + -5z

Solving
2z = 1 + -5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '5z' to each side of the equation.
2z + 5z = 1 + -5z + 5z

Combine like terms: 2z + 5z = 7z
7z = 1 + -5z + 5z

Combine like terms: -5z + 5z = 0
7z = 1 + 0
7z = 1

Divide each side by '7'.
z = 0.1428571429

Simplifying
z = 0.1428571429

See similar equations:

| 7x+6.95=74.15 | | 7(4x-9)-13=-87 | | 6(x-1)=5 | | 2.3-5x=31-5x | | 8y^4-24y^3+18y^2= | | 99-9k=9k-27 | | 4x-3y=28 | | 14z^2-3=21z-7 | | 12+120037= | | 2x+1=2x-10 | | 4c-12=6c | | 14z^2-3=21z+7 | | x^5-36x=0 | | 6=-(3x+6) | | -8x+2x^2=0 | | 113=2l+2(28.5) | | -(x-9)=-4 | | 18-4q=-6 | | 16x^2-16x+7=0 | | 256x^4-81y^4=0 | | 30-4x=40-8x | | 8k-3=-9-6k | | 125x^3-216y^3= | | =2z^2+7z-4 | | 5n+3=3(1-2n) | | 5(x-4)=3(x+4) | | -9=-0.9m | | 6[5-8r]+12=-54 | | 2x^2-12xy+7y^2-44=0 | | .05x+.30(200)=.10(x+200) | | [599353-93745]= | | X^2+20=10x |

Equations solver categories